Gender representation in the textbook for vocational school students in the Indonesian EFL settings (ELT Forum: Journal of English Language Teaching, 2022)
A textbook is expected to cover all of the teaching necessities as well as educational values contained in the curriculum. Conversely, many scholars or researchers in the study of gender representation portrayed English language textbooks tend to have gender-biased in terms of gender representation in which males are represented more than females in many aspects. Hence, investigating how males and females are represented in Indonesian EFL textbooks is highly beneficial to be explored to clarify and update the finding based on the previous studies. The concern of this current study is to investigate gender representation in the Indonesian EFL textbook for vocational school students by using the framework proposed by (Amerian & Esmaili, 2014). The analysis of the data is based on critical discourse analysis and content analysis. Surprisingly, congruent with most previous studies, the finding reflects that there is inequality in terms of gender representation in which females are underrepresented in the textbook. The finding of this recent study pinpoints the depiction of how males and females are represented and depicted in the Indonesian EFL textbook, as a result, it is expected to convey the awareness of scholars, educators, textbook writers or designers, and policymakers as well related to this issue. Then, it is still highly suggested for scholars or researchers in future studies exploring gender representation in Indonesian EFL textbooks by using other books or other levels of education to evaluate the development of this issue.